Private Acts in Public Places : A Social History of Divorce in the Formative Era of American Family Law - Chused, Richard H. (Book collections on Project MUSE., 2015)
Richard H. Chused examines more than 1300 petitions for divorce in Maryland filed during the first half of the nineteenth century. By weaving together information on the legislative handling of these petitions, the voting patterns of the state legislators, and the judicial treatment of related disputes, Chused shows the connections between politics, regional differences, and the development of American family law. His analysis also provides valuable insights into the social history of the time, a period when traditional Southern family values were at odds with the more modern values brought about by urbanization.